Nahdlatul Ulama's Ijtihad Method in Fatwa: Analysis of the Content of Legal Decisions and their Validity in Indonesia - Ismail Jalili; Fadillah Ulfa; Mualimin Mochammad Sahid (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
This research aimed to investigate the method of inference in Nahdatul Ulama Scholars to issue fatwas regarding some issues in Indonesia. This research applied the qualitative method to collect data for looking into the topic and using a content analysis approach to analyze the legal decision of Nahdatul Ulama scholars and its validity as a product of fatwa. The results show that the inference done by Nahdatul Ulama scholars did not correspond to the belief done by the Muslim scholars in the past era due to their shortcomings in fulfilling the requirement of Mujtahid Muthlaq. This research also reveals that their method can be categorized as ijtihad jama’i, and the validity of the fatwas was significant enough for the Indonesian Muslim society to perform their daily ibadah or muamalah activities. This research contributes to the existing body of literature by providing insights into the specific inference method employed in Indonesia. It focuses on the influence of fatwas issued by scholars affiliated with Nahdatul Ulama, highlighting their significant following among ordinary individuals associated with this organization.